2021
DOI: 10.3390/pr9071167
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physical Characteristics of Typical Maize Seeds in a Cold Area of North China Based on Principal Component Analysis

Abstract: The physical properties of maize seeds are closely related to food processing and production. To study and evaluate the characteristics of maize seeds, typical maize seeds in a cold region of North China were used as test varieties. A variety of agricultural material test benches were built to measure the maize seeds’ physical parameters, such as thousand-grain weight, moisture content, triaxial arithmetic mean particle size, coefficient of static friction, coefficient of rolling friction, angle of natural rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Principal component analysis (PCA) is a statistical method that transforms multi-index into a few comprehensive indexes by using the idea of dimension reduction (Xin et al, 2019 ; Wang X. K. et al, 2020 ; Bi et al, 2022 ). These comprehensive indicators retain most of the information of the original indicators (Shi et al, 2021 ; Tang et al, 2021 ). The Kaiser–Meyer–Olkin (KMO) value was 0.582 and Bartlett's sphericity test was p < 0.001, indicating that PCA could be performed (Hao et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Principal component analysis (PCA) is a statistical method that transforms multi-index into a few comprehensive indexes by using the idea of dimension reduction (Xin et al, 2019 ; Wang X. K. et al, 2020 ; Bi et al, 2022 ). These comprehensive indicators retain most of the information of the original indicators (Shi et al, 2021 ; Tang et al, 2021 ). The Kaiser–Meyer–Olkin (KMO) value was 0.582 and Bartlett's sphericity test was p < 0.001, indicating that PCA could be performed (Hao et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…A similar study reported by also showed that magnetization treatment effectively alleviated the inhibitory effect of salt water irrigation on the growth of grape stems and leaves. Zhao et al (2021) reported that magnetized water irrigation increased plant height, leaf area index, and dry matter accumulation of winter wheat.…”
Section: E Ects Of Irrigation Treatments On Growth Indexes Of H Ammod...mentioning
confidence: 99%
“…The square box with grains or stems was placed on the right side of the plate surface and the angle adjusting device was slowly rotated to tilt the stainless-steel plate. When the square box (with grains or stems) started to rotate, the rotation angle was recorded [41,42]. The static friction coefficients of the rice grains and stems with different configurations were measured once.…”
Section: Measurement Of Static Friction Coefficientmentioning
confidence: 99%
“…However, the chroma and hue ranged from 1.63 to 15.84 and 26.80 to 92.81, respectively. The seeds with similar physical attributes like colour can be pooled in one group through clustering methods and then comprehensively evaluated (Tang et al 2021). The other morphological characters like dent corn or quality traits like waxy corn or sweet corn also have been considered for comparative evaluation on the physical basis (Coskun et al 2006, Sharma et al 2017.…”
mentioning
confidence: 99%